Pseudogastropods - Aurele La Rocque (Hello World!, 1973)
Valvata arenifera turned out to be a caddis case and is well known to collectors of freshwater gastropods working in lakes with sandy bottoms. There is another group of well known pseudogastropods belonging to the genus Spirorbis that is familiar to marine malacologists and students of fossil gastropods. Occasional notes on fossil Spirorbis appear in the paleontological literature but no mention is made, to my knowledge, of the operculum, at least in North American references.